Base controlled rongalite-mediated reductive aldol/cyclization and dimerization of isatylidene malononitriles/cyanoacetates - Chaudhari, Suryakant S.; Nichinde, Chandrakant B.; Patil, Baliram R.; Girase, Amardipsing S.; Rama Krishna, Gamidi; Kinage, Anil K. (Organic and biomolecular chemistry, 2024)
In this study, we developed a novel methodology involving a base-controlled, rongalite-mediated reductive/aldol reaction, followed by cyclization of isatylidene malononitriles/cyanoacetates, resulting in the synthesis of spiro[2,3-dihydrofuran-3,3 `-oxindole]. Additionally, we have disclosed a rongalite-mediated dimerization process for isatylidene malononitriles, yielding dispiro[cyclopent-3 `-ene]bisoxindole. The utilization of rongalite in this reaction serves a dual purpose, acting both as a reducing agent and a C1 synthon. The developed approach has several advantages like a simple reaction setup, a wide substrate scope, requiring less time, using water as a green solvent, no metal or catalyst is required and products can be easily isolated via filtration with excellent yields under mild reaction conditions. A novel methodology was developed for the synthesis of spiro[2,3-dihydrofuran-3,3 `-oxindole] and dispiro[cyclopent-3 `-ene]bisoxindole under mild reaction conditions using inexpensive reagents.

Bronsted acid-promoted cyclodimerization of α,β-unsaturated γ-ketoesters: construction of fused pyrano-ketal-lactones and γ-ylidene-butenolides - Vinodkumar, Ramavath; Nakate, Ashwini K.; Sharma, Himanshu; Vanka, Kumar; Rama Krishna, Gamidi; Kontham, Ravindar (ACS Omega, 2024)
Unprecedented MsOH-promoted diastereoselective cascade dimerization and intramolecular lactonization of readily accessible alpha,beta-unsaturated gamma-ketoesters are presented. The results obtained in this work, control experiments, and density functional theory (DFT) calculations suggested that the initial enolization and E to Z isomerization/equilibration of olefin (C=C) of substrate alpha,beta-unsaturated gamma-ketoesters give a Z-isomer preferentially over an E-isomer. Subsequently, the Z-isomer undergoes intermolecular annulation with alpha,beta-unsaturated gamma-ketoesters via domino Michael addition/ketalization/lactonization steps to furnish fused tetracyclic pyrano-ketal-lactone. However, the Z-isomer prefers intramolecular trans-esterification in a competing pathway and gives bicyclic gamma-ylidene-butenolide. The key features of this work include simple Br & oslash;nsted acid catalysis, the formation of three bonds, two rings, and three contiguous stereogenic centers in a single step, DFT calculations, and the assignment of relative stereochemistry through X-ray diffraction (XRD) and two-dimensional (2D) nuclear magnetic resonance (NMR) analyses.